2016
DOI: 10.4142/jvs.2016.17.3.385
|View full text |Cite
|
Sign up to set email alerts
|

Establishment of a canine mammary gland tumor cell line and characterization of its miRNA expression

Abstract: Canine mammary gland tumors (CMGTs), which are the most common neoplasms in sexually intact female dogs, have been suggested as a model for studying human breast cancer because of several similarities, including relative age of onset, risk factors, incidence, histological and molecular features, biological behavior, metastatic pattern, and responses to therapy. In the present study, we established a new cell line, the SNP cell line, from a CMGT. A tumor formed in each NOD.CB17-Prkdcscid/J mouse at the site of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 21 publications
2
27
0
Order By: Relevance
“…One interesting finding in our transcriptome profile was the overexpression of miRNA precursor genes such as cf‐mir‐374b , cf‐mir‐145 and cf‐mir‐23b . Indeed, cfa‐mir‐145 had already been described in a primary culture of canine mammary cancer, where it was found 993.4‐fold over normal mammary gland tissue expression . The mir‐374b was associated to malignant behaviour in human gastric cancer and was suggested as a potential prognostic marker in cervical cancer, while mir‐23b was found downregulated in human colon cancer maybe acting as a modulator suppressor of metastasis .…”
Section: Discussionmentioning
confidence: 99%
“…One interesting finding in our transcriptome profile was the overexpression of miRNA precursor genes such as cf‐mir‐374b , cf‐mir‐145 and cf‐mir‐23b . Indeed, cfa‐mir‐145 had already been described in a primary culture of canine mammary cancer, where it was found 993.4‐fold over normal mammary gland tissue expression . The mir‐374b was associated to malignant behaviour in human gastric cancer and was suggested as a potential prognostic marker in cervical cancer, while mir‐23b was found downregulated in human colon cancer maybe acting as a modulator suppressor of metastasis .…”
Section: Discussionmentioning
confidence: 99%
“…In veterinary medicine, a few analyses of the miRNA expression levels in tissues of canine mammary tumors (CMT) have been published [ 119 , 120 , 123 , 124 ]. In one study, nine of ten miRNAs studied (miR-15a, miR-16, miR-17-5p, miR-21, miR-29b, miR-125b, miR-145, miR-155, miR-181b, let-7f) that are involved in human breast cancer appeared to have the same expression pattern in CMTs [ 119 ].…”
Section: Mirnamentioning
confidence: 99%
“…Other in vitro studies have suggested miR‐143 and miR‐138a are dysregulated in some CMT cells, and that miR‐141 plays a role in CMT development by inhibiting tumor suppressor INK4A. [ 15,16 ]…”
Section: Introductionmentioning
confidence: 99%